Entrepreneurship Development on Poverty Reduction in Nigeria - Lawal Suleiman Gbenga; Rufus Emmanuel-Ubong Ita; Bassey Gift Eja; Eno Omini Ojah; Cecilia James Okon (Law and Economy, 2023)
The study investigated entrepreneurship development on poverty alleviation in Nigeria. Desk survey method was used to gather relevant information while chi-square tool was adopted to statistically analyze the relationship between entrepreneurship development and poverty alleviation. The findings revealed that entrepreneurial activities had a significant relationship with poverty alleviation; there was a significant relationship between entrepreneurship and economic growth and poverty alleviation; there was a significant relationship between entrepreneurship effectiveness and efficiency with poverty alleviation. Based on these findings, the study recommended that government should implement strategies that will help to support micro-credit and employment opportunities. The study recommended that entrepreneurs need to be innovative and creative and its activities should be a key component to increasing living standards.